2008
DOI: 10.1590/s0004-282x2008000400009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between migraine subtipes and depression

Abstract: -This study has evaluated depression in patients with episodic migraine (n=98), chronic migraine without medication overuse (n=23), and chronic migraine with medication overuse (n=57). The Beck Depression Inventory (BDI) was used to evaluate depressive symptoms in these three groups. The mean BDI score obtained in all patients was higher than that observed in asymptomatic subjects (episodic migraine=16.09±11.79, chronic migraine with medication overuse=18.91±12.53, chronic migraine without medication overuse=1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Our sample was also similar to the population norms for scores on the BDI 41 . As expected, scores were higher in individuals with migraine relative to controls 42,43 .…”
Section: Discussionsupporting
confidence: 76%
“…Our sample was also similar to the population norms for scores on the BDI 41 . As expected, scores were higher in individuals with migraine relative to controls 42,43 .…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have demonstrated an association between migraine, anxiety and depression [ 5 – 10 ]. Researchers have proposed that the relationship between migraine, depression and anxiety is bi-directional, that is that they both influence each other [ 11 , 12 ]. Previous work has also demonstrated that migraine patients are more light sensitive (“photophobic”) than control subjects [ 15 , 21 23 ], in some cases even between attacks [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that the presence of psychiatric co-morbidities is increased in people with migraine, especially depression and anxiety [ 5 – 10 ]. There seems to be a bi-directional relationship between migraine and depression, with each disorder increasing the risk of the other [ 11 , 12 ]. Photophobia also was reported in patients with depression [ 13 ], but the nature of this relationship has not been rigorously studied.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, data regarding the relationship between migraine and mood/anxiety disorders is scarce . One did evaluate the association of headache and psychiatric disorders in a population sample in the city of São Paulo and classified the study participants according to their psychiatric condition using The World Health Organization Composite International Diagnostic Interview .…”
Section: Discussionmentioning
confidence: 99%